Perancangan Website SDIT Harapan Ummat Menggunakan Metode Waterfall untuk Mendukung Media Informasi dan Promosi Sekolah - Muhammad Fikri Az Zuhdi; Edi Wibowo (DBESTI: Journal of Digital Business and Technology Innovation, 2026)
A school website was an important tool for delivering information to the community effectively and efficiently. However, SDIT Harapan Ummat did not have an official digital platform that could be used for promotional purposes and to provide information about student admissions (PPDB). This research aimed to design and develop a school website based on the WordPress CMS as a medium for disseminating information and promoting SDIT Harapan Ummat. The development method used in this study was the waterfall model, which included requirements analysis, design, development, testing, and maintenance. The tools used included WordPress, Elementor, and Table Addons for Elementor. The testing phase involved two methods: black box testing to verify system functionality and usability testing using a likert scale to assess user experience. The test results showed that all website features functioned properly and no operational issues were encountered. Usability testing conducted with five respondents resulted in an average score of 4.55, which was categorized as very good. Based on these findings, it was concluded that SDIT Harapan Ummat website was successfully developed according to user needs and provided a satisfying user experience. The website was also considered suitable to serve as a school information platform that was easily accessible to the public.